Examining a Dual‐Process Model of Desensitization and Hypersensitization to Community Violence in African American Male Adolescents. Issue 5 (12th October 2017) - Gaylord‐Harden, Noni K.; Bai, Grace J.; Simic, Dusan
Abstract: The purpose of the current study was to examine a dual‐process model of reactivity to community violence exposure in African American male adolescents from urban communities. The model focused on desensitization and hypersensitization effects as well as desensitization and hypersensitization as predictors of aggressive behavior. Participants were 133 African American male high school students, mean age = 15.17 years, SD = 0.96. Participants completed measures of exposure to community violence, depressive symptoms, hyperarousal symptoms, aggressive beliefs, and aggressive behaviors at two time points. Community violence exposure predicted changes in aggression, β = .25, p = .004, and physiological arousal, β = .22, p = .010, over time, but not aggressive beliefs. The curvilinear association between community violence exposure and changes in depression over time was not significant, β = .42, p = .083, but there was a significant linear association between the exposure to community violence (ECV) and changes in levels of depression over time, β = .21, p = .014. Results indicated a significant mediation effect for hyperarousal on the association between community violence exposure and aggressive behavior, B = 0.20, 95% CI = [0.04, 0.54]. Results showed support for physiological hypersensitization, with hypersensitization increasing the risk for aggressive behavior.